Recent advances in the biotechnological production of erythritol and mannitol. (3rd July 2020) - Martău, Gheorghe Adrian; Coman, Vasile; Vodnar, Dan Cristian
Abstract: Dietary habits that include an excess of added sugars have been strongly associated with an increased risk of obesity, heart disease, diabetes, and tooth decay. With this association in view, modern food systems aim to replace added sugars with low calorie sweeteners, such as polyols. Polyols are generally not carcinogenic and do not trigger a glycemic response. Furthermore, owing to the absence of the carbonyl group, they are more stable compared to monosaccharides and do not participate in Maillard reactions. As such, since polyols are stable at high temperatures, and they do not brown or caramelize when heated. Therefore, polyols are widely used in the diets of hypocaloric and diabetic patients, as well as other specific cases where controlled caloric intake is required. In recent years, erythritol and mannitol have gained increased importance, especially in the food and pharmaceutical industries. In these areas, research efforts have been made to improve the productivity and yield of the two polyols, relying on biotechnological manufacturing methods. The present review highlights the recent advances in the biotechnological production of erythritol and mannitol and summarizes the benefits of using the two polyols in the food and pharmaceutical industries.